1991
DOI: 10.1093/carcin/12.2.311
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alternating dietary restriction and ad libitum feeding of mice on the development of diethylnitrosamine-induced liver tumours and its correlation to insullnaemia

Abstract: The effects of alternating ad libitum feeding and 30% restriction of the dietary intake on the development of diethylnitrosamine (DEN)-induced hepatic neoplasia were investigated. Dietary restriction retarded the growth of glucose-6-phosphatase-deficient (G6Pd) preneoplastic foci and subsequently that of hepatocellular adenomas and adenocarcinomas. The number of foci in standardized liver sections increased from 4.44 foci/cm2 at 12 weeks to 9.65 foci/cm2 at 24 weeks in ad libitum fed animals but only from 2.35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This is in addition to the noted delay/suppression by CR on these pathologies (30 -32, 54). Of particular interest is that in a previous study, CR was able to retard the development of diethylnitrosamine-induced tumors in the livers of mice (55). In this study, age-related insulinaemia reflecting resistance of tissues to the effects of insulin was much greater for AL vs. CR mice and correlated with the number of liver foci.…”
Section: Discussionmentioning
confidence: 49%
“…This is in addition to the noted delay/suppression by CR on these pathologies (30 -32, 54). Of particular interest is that in a previous study, CR was able to retard the development of diethylnitrosamine-induced tumors in the livers of mice (55). In this study, age-related insulinaemia reflecting resistance of tissues to the effects of insulin was much greater for AL vs. CR mice and correlated with the number of liver foci.…”
Section: Discussionmentioning
confidence: 49%
“…In these studies, starting DR 4 months after the carcinogenic insult resulted in an elimination of the carcinogenic action of the agent. Other experiments have shown that DR can not only slow the growth of diethylnitrosamine (DEN)-induced preneoplastic foci in liver, but can even induce foci regression (43). The mechanism(s) important for the inhibition of spontaneous tumorigenesis may also be important for this effect of DR on induced tumorigenesis.…”
Section: Dietary Restriction and Induced Carcinogenesismentioning
confidence: 99%
“…Studies using dietary restriction (DR) in mice which is a classic experimental model to inhibit cancer development showed that DR was associated with a marked reduction in circulating IGF-I levels. The growth of chemically-induced liver tumours in mice was also inhibited by diet restriction and this was accompanied by a decrease in IGF-I concentrations [102]. Dietary restriction in mice has also been shown to increase apoptotic rates and reduce progression of bladder cancers, that was similarly associated with reduced levels of circulating IGF-I and in this study the positive impact of dietary restriction was inhibited when IGF-I levels were restored indicating a key role for IGF-I in mediating the effects of nutrition on tumour progression [103].…”
mentioning
confidence: 99%